Increased exosome secretion in neurons aging in vitro by NPC1-mediated endosomal cholesterol buildup - Guix, Francesc X. (2021)
As neurons age, they show a decrease in their ability to degrade proteins and membranes. Because undegraded material is a source of toxic products, defects in degradation are associated with reduced cell function and survival. However, there are very few dead neurons in the aging brain, suggesting the action of compensatory mechanisms. We show in this work that ageing neurons in culture show large multivesicular bodies (MVBs) filled with intralumenal vesicles (ILVs) and secrete more small extracellular vesicles than younger neurons. We also show that the high number of ILVs is the consequence of the accumulation of cholesterol in MVBs, which in turn is due to decreased levels of the cholesterol extruding protein NPC1. NPC1 down-regulation is the consequence of a combination of upregulation of the NPC1 repressor microRNA 33, and increased degradation, due to AktmTOR targeting of NPC1 to the phagosome. Although releasing more exosomes can be beneficial to old neurons, other cells, neighbouring and distant, can be negatively affected by the waste material they contain.